(untitled) (European Journal of Formal Sciences and Engineering, 2021)
Time management and control are crucial for project success, and it has known an increasing interest by researchers around the world since the appearance of project management and until now. The aim of the present paper is to provide a comprehensive overview of researches in this field. A bibliometric analysis of researches in time management and control published in the Web of Science (WoS) during 2012-2021 was conducted in order to find the most influential publications in this field, as well as, the countries that contribute the most to these researches, and the most used key words. The VOS Viewer was used for mapping and visualizing bibliometric networks. The results show an increased trend of publications in this field. And that the major contributors to researches in Time Management and Control are People’s Republic of China, the United States of America, and England. Moreover, Labadie (2004) was the most cited author. Also, the results show 3 main levels of keywords, the first was related to time management in general, the second was related to the models and systems using and the third concerning the tools, the methods used in time management and control. These findings could help researchers to understand more the topic of time management and control, and it opens up the scope of view to conduct studies in related fields.